2021
DOI: 10.1002/mp.14764
|View full text |Cite
|
Sign up to set email alerts
|

Machine QA for the Elekta Unity system: A Report from the Elekta MR‐linac consortium

Abstract: Over the last few years, magnetic resonance image-guided radiotherapy systems have been introduced into the clinic, allowing for daily online plan adaption. While quality assurance (QA) is similar to conventional radiotherapy systems, there is a need to introduce or modify measurement techniques. As yet, there is no consensus guidance on the QA equipment and test requirements for such systems. Therefore, this report provides an overview of QA equipment and techniques for mechanical, dosimetric, and imaging per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(134 citation statements)
references
References 80 publications
3
120
0
11
Order By: Relevance
“…Results for the various isocentre measurement techniques are presented in Table 1. All techniques showed that the isocentre was within the tolerance (≤ 0.50 mm [3]).…”
Section: Isocentre Diametermentioning
confidence: 82%
See 4 more Smart Citations
“…Results for the various isocentre measurement techniques are presented in Table 1. All techniques showed that the isocentre was within the tolerance (≤ 0.50 mm [3]).…”
Section: Isocentre Diametermentioning
confidence: 82%
“…3(c)) images are not discernible from the nominal (no angular offset) image without further analysis of pixel intensity pro les. Obviously, visual inspection cannot be used to determine the absolute gantry angle; however, it is useful for determining if set positions are within the tolerance speci ed by Roberts et al [3] (± 0.3°). Note that the more recent publication of Woodings et al [5] suggests a speci cation of < 0.2° for gantry angle, which cannot be achieved with this methodology unless further analysis is performed on the pixel intensity pro les, discussed below.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations